Le katajjaq : un jeu inuit traditionnel - Beaudry, Nicole (Études Inuit Studies, 1978)
Katajjaq, a traditional Inuit game Katajjait — the traditional Inuit throat-games — display unusual musical properties and for that reason they have been submitted to extensive musicological analysis. Furthermore, they also constitute a particularly rich example of traditional Inuit game behaviour. The present article aims at backing that statement through an analysis of Inuit games from Central Arctic, based on available written information¹.This analysis enables us to define the katajjaq not only in terms of formal properties, but also in terms of social functions. This analytical definition is achieved by comparing katajjaq with some of the Inuit game mechanisms. le katajjaq, un jeu inuit traditionnel Le katajjaq ou jeu de gorge inuit à l'origine lointaine, se caractérise par des propriétés musicales exceptionnelles. Ce jeu vocal a donc fait l'objet d'analyses musicologiques approfondies. Par ailleurs, il illustre particulièrement bien le système ludique inuit traditionnel. Nous cherchons ici à confirmer cette hypothèse, à la suite d'une étude par les textes¹ sur les jeux inuit de l'Arctique central en général. A la lumière de cette étude, nous tâchons de définir le jeu de gorge, tant par ses fonctions sociales que par son comportement formel et ce, en comparaison avec quelques mécanismes des jeux inuit traditionnels.
Publisher: Association Inuksiutiit Katimajiit Inc.

Toward Transcription and Analysis of Inuit Throat-Games: Macro-Structure - Beaudry, Nicole (Ethnomusicology, 1978)
Publisher: University of Illinois Press